Balance hídrico diario de la microcuenca hidrográfica del Río Malacatos en la provincia de Loja - Campoverde Salas, Miguel Angel (2019)
The research was carried out at the Malacatos microbasin level, located in the canton and province of Loja. The study period was two years, from the month of January 2016 to December 2017, the daily water balance was determined by means of water inflows and outflows that the cause possesses through the data of eight nearby pluviometric stations; The area where there is a greater rainfall was identified, which allowed establishing a conservation project. The missing data from the stations were filled in by means of the Climatol statistical package of R version 3.1.1. With the complete data, the information was processed to generate the raster of precipitation, runoff, evapotranspiration and infiltration using the spatial analysis programs, this allowed to formulate the water balance formula. The results indicate that the water storage of the basin is constant due to the high rainfall of up to 4.1 mm per day and greater than 80 mm per month with its subsequent runoff to the middle and lower part; This result allows us to propose a conservation proposal for the microbasin through the production of fruit trees since the area has maximum temperatures of up to 32 oC in summer, which would allow the development of fruit species. This study allowed to verify that the microbasin has a well-defined rainfall regime, as well as the direct incidence of evapotranspiration in the reserve and flow of the resource; what is exposed in the present investigation. Keywords: Water Balance, Climatol Package